Experimental and Numerical Study Determining the Warpage Phenomenon of Thin-Wall Injection Molding - Yueh-Tzu Huang; Chiung-Fang Huang; Bou-Yue Peng; Chun-Wei Chang; Hsing-Chung Cheng; Yi Lin; Yung-Kang Shen; Hao Wang (Advances in Polymer Technology)
This study emphasizes the warpage phenomenon of thin-walled parts using acrylonitrile-butadiene styrene (ABS) plus polycarbonate (PC) plastics for optimal processing by thin-wall injection molding. The authors first employed the Moldflow software to analyze the runner’s balance on multicavities for thin-walled parts and to simulate the warpage of thin-walled parts with thin-wall injection molding. Then, this study used those data to fabricate a real mold by computer numerical control machining. For this study, the authors fabricated thin-walled parts and measured their warpage using various process parameters (injection speed, injection pressure, mold temperature, packing time, and melt temperature) with thin-walled injection molding. Finally, the authors found that the most important processing parameter was the packing time for warpage phenomenon of thin-walled parts by thin-wall injection molding.